The Folded Buccal Musculomucosal Flap for Large Palatal Fistulae in Cleft Palate - Kobayashi, Shinji (Wolters Kluwer Health, 2014)
BACKGROUND: A palatal fistula is a common complication of cleft palate repair. Although a buccal musculomucosal flap (BMMF) is effective for fistula repair, it does have the following problems: a second operation may be required to release the pedicle on the oral side and unilateral BMMF cannot close mucosal defects of both the nasal and oral sides. A novel fistula closure method using the folded BMMF (f-BMMF) invented by the authors is presented. CASE: A 8-year-old-boy with bilateral cleft lip and palate with anencephaly. A fistula in the hard palate occurred after palatoplasty by the Furlow method, and an f-BMMF was planned. The mucosal defects of the nasal and oral sides were covered by 2 separate islands of mucosal epithelium. Finally, no reoperation was needed to remove the pedicle of the f-BMMF. CONCLUSION: The f-BMMF is able to cover both sides without a raw surface and a mucosal graft even in cases of large fistula closure, although BMMF cannot usually cover both oral and nasal sides of a fistula. The advantages of this procedure are that it does not require second surgery to release the pedicle and that its distal island mucosa can be used to monitor engraftment. This proposed method seems to be an appealing alternative.